Sistem Monitoring Kondisi Asset Berbasis Android - salamun salamun; gianto Gianto; Luluk Elvitaria (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2019)
As a means of supporting the lecture process, the Abdurrrab University Informatics Engineering Study Program has a computer laboratory. But in monitoring its assets are still carried out conventionally. In the era of technology as it is today, this method is felt to be less effective. In addition to the problem of physical archives that require space and risk of losing files, data management is an important issue in this regard. To overcome this problem, we need an Android-based Laboratory Asset Monitoring System which data management is centralized to the database. In this Laboratory Asset Monitoring System, the admin can input data in the form of asset data and user data. The data inputted by the admin is then stored in a database and processed by the system into asset information such as asset life information and asset depreciation and user information. To calculate depreciation of assets, this system uses the Straight Line Depreciation Method. While laboratory personnel can check assets regularly to find out the current condition and status of assets. Asset checking data will also be saved to the database and can be called whenever needed.